مفاهيم الثقافة والمصطلحات المرتبطة بها - خواني, خالد (جامعة الوادي - University of Eloued, 2021)
كثرت المفاهيم والدلالات المتعلقة بالثقافة، وقد تعدد المفكرون في شتى التخصصات الذين عالجوا مفهومها آخذين بعين الاعتبار التحوّلات والخصوصية والعوامل الفاعلة في كافة المجتمعات البشرية. من خلال هذه الورقة البحثية نحاول التعرض لمختلف مفاهيم الثقافة والمصطلحات المرتبطة بها والمتداولة عند أهم المفكرين الذين تناولوها بإسهاب محاولين التقريب بين هذه المفاهيم الخاضعة للتخصص وللزاوية الذي ينظر من خلالها كل مفكر. There are a multitude of concepts related to culture, and thinkers in various disciplines have dealt with this concept taking into account the changes in privacy and factors active in all human societies. Through this study we try to address the different concepts related to culture and the terminology associated with it, which are used by thinkers, trying to relate these concepts that are the subject of specialization and through which each thinker approaches it according to his vision.
مقال
Keywords: ثقافة ; مفاهيم ; مصطلح ; أنثروبولوجيا ثقافية; culture ; concepts ; term ; cultural anthropology